Shariah Juristical Effect of Gharar in Predetermining Takaful Contribution - Lambak, Salman (2013)
The paper attempts to ascertain theact of applying gharar (risk) in predetermining Takaful contribution (premium) hence to offera juristic opinion from Islamic Shariah perspective. The general concept of gharar will be comprehended and briefly compared with the concept of risk. Subsequently, the act of making a gharar in fixing the Takaful contribution will bedebated and juristically analysed. The paper, however, does not attempt to reassess the Muslim jurists’ ruling on the permissibility of neither insurance nor takaful.It is concluded that the gharar (risk) in principle is a subject that is recognized in Islam. It would then lead to main inference that making a gharar (risk) asa consideration in contribution calculation is permissible from Shariah perspective.